2016
DOI: 10.1039/c5sm02313k
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of weak polyelectrolyte multilayers in response to organic solvents

Abstract: Weak polyelectrolyte multilayers (PEMs) prepared by the layer-by-layer assembly technique have recently been found to demonstrate a unique contraction upon exposure to organic solvents. This response is dependent upon which organic solvent is employed, and fundamental questions have not been clarified regarding the correlation of the magnitude of the film contraction with solvent type. In this work, we used solubility parameters to analyze the response of branched poly(ethylene imine)/poly(acrylic acid) (BPEI/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Nanocoating thickness was measured in different environments as a function of the number of BL deposited (Figure S2, Supporting Information). A swelling ratio of 52% was observed for an 8‐BL PEI/PAA nanocoating when immersed in water, which agrees well with a previous study . The film shrinks to its original thickness (≈700 nm for 8‐BL) after drying at 70 °C for 30 min.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Nanocoating thickness was measured in different environments as a function of the number of BL deposited (Figure S2, Supporting Information). A swelling ratio of 52% was observed for an 8‐BL PEI/PAA nanocoating when immersed in water, which agrees well with a previous study . The film shrinks to its original thickness (≈700 nm for 8‐BL) after drying at 70 °C for 30 min.…”
Section: Resultssupporting
confidence: 91%
“…A swelling ratio of 52% was observed for an 8-BL PEI/PAA nanocoating when immersed in water, which agrees well with a previous study. [51] The film shrinks to its original thickness (≈700 nm for 8-BL) after drying at 70 °C for 30 min. It has been reported that this reversible swelling-drying cycle can be repeated at least ten times without damaging the multilayer nanocoating.…”
Section: Resultsmentioning
confidence: 99%
“…We have successfully applied a new swelling model, a model based on Painter‐Shenoy for gel‐like swelling that incorporates the Leibler‐Sekimoto theory for Langmuir sorption, to extract the network parameters of the polyamide thin films. We anticipate that this proposed model can be applied to a variety of heterogeneous polymeric materials where swelling behavior is a function of physical properties, such as polyelectrolyte layer‐by‐layer films, polymer brushes, nanophase segregated materials, as well as polymer glasses.…”
Section: Discussionmentioning
confidence: 99%
“…The exact reasons for this SA‐induced performance improvement are still unknown. It may be speculated that this SA process helps to remove loose polymer structures or rearranges polymer chains by dehydration . SA can also prevent the collapse of pores in the support and facilitate the solvent entrance into the pores .…”
Section: Resultsmentioning
confidence: 99%